EFFECT OF SOWING DATES ON GROWTH AND YIELD OF GREENGRAM (Vigna radiata L.) UNDER RAINFED SITUATION - P. RAGHURAMI REDDY, S. SRINIVASA RAO, D. SHIVANI, V. SRIDHAR and (The Journal of Research, PJTSAU, 2019)
A field experiment was conducted during kharif, 2015 and 2016 at Agricultural Research Station, Madhira, Khammam district, Telangana to study the effect of optimum time of sowing in greengram. The experiment consisted of six dates of sowing (3rd wk of June, 1st wk of July, 3rd wk of July, 1st wk of August, 3rd wk of August and 1st wk of September) with three replications in randomized block design. Two years of study and pooled data at harvest showed that significantly higher plant height was recorded when greengram was sown in 3rd wk of June followed by 1st wk of July and higher drymatter was produced with 3rd wk of June followed by 1st wk of July sowing except in 2015 both were at par with each other. Sowing dates exerted significant effect on yield attributes (Clusters/plant, Pods/plant, Seeds/pod and Test weight) and seed yield of greengram were significantly higher in 3rd wk of June followed by 1st and 3rd wk of July compared to other dates of sowing in kharif season during two years and pooled.